Patient Views Around Their Hernia Surgery: A Worldwide Online Survey Promoted Through Social Media - East, Barbora; Hill, Susannah; Dames, Nicola; Blackwell, Sue; Laidlaw, Lynn; Gök, Hakan; Stabilini, Cesare; de Beaux, Andrew (Frontiers in Surgery, 2021)
Introduction: Hernias are one of the most common surgical diagnoses, and general surgical operations performed. Patients’ involvement in the decision making can be limited. The aim of this study was to explore patients’ perspectives around their hernia and its management, to aid future planning of hernia services to maximise patient experience and good outcomes for the patient. Methods: A SurveyMonkey questionnaire was developed by patient advocates with some advice from surgeons. It was promoted on Twitter and Facebook, including all found ‘hernia help’ groups on these platforms over a six-week period during the summer of 2020. Demographics, the reasons for seeking a hernia repair, decision making around the choice of surgeon, hospital, mesh type, pre-habilitation, complications and participation in a hernia registry were collected. Results: 397 questionnaires were completed in the study period. The majority of cases were from English speaking countries. There was a strong request for hernia specialists to perform the surgery, to have detailed knowledge about all aspects of hernia disease and its management, including no operation and non-mesh options. Chronic pain was the most feared complication. The desire for knowledge about the effect of the hernia and surgery on sexual function in all age groups was a notable finding. Pre-habilitation and a hernia registry participation were well supported. Conclusions: Hernia repair is quality of life surgery. Whether awaiting surgery, or having had surgery with a good or bad outcome, patients want information about their condition and treatment, including the effect on aspects of life such as sex, and they wish greater involvement in their management decisions. Patients want their surgery by surgeons who can also manage complications of such surgery or recommend further treatment. A large group of ‘hernia surgery injured’ patients feel abandoned by their general surgeon when complications ensue.